Trainyourbrain, a Mental Preparation Programme to Optimise Clarity and Commitment in Matches - Bernier, Marjorie; Haffner, Kévin; Bagot, Pierre; Doron, Julie (Réflexions Sport, 2024)
Mindfulness is an approach of mental preparation that enables athletes to develop awareness, acceptance, and refocusing skills. In TrainYourBrain project we implemented a mindfulness program integrated into elite fencing training. In this article, we present the principles and benefits of mindfulness for performance, as well as the preliminary results of the TrainYourBrain program. We also offer some recommendations to promote athletes’ adherence to this type of program.
Keywords: mindfulness; commitment; fencing; adherence; mental preparation